2013
DOI: 10.2196/jmir.2094
|View full text |Cite
|
Sign up to set email alerts
|

Health Professional Learner Attitudes and Use of Digital Learning Resources

Abstract: BackgroundWeb-based digital repositories allow educational resources to be accessed efficiently and conveniently from diverse geographic locations, hold a variety of resource formats, enable interactive learning, and facilitate targeted access for the user. Unlike some other learning management systems (LMS), resources can be retrieved through search engines and meta-tagged labels, and content can be streamed, which is particularly useful for multimedia resources.ObjectiveThe aim of this study was to examine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 8 publications
2
35
0
Order By: Relevance
“…A second year student (15) explained in relation to question one that the LC "Offers guidance of the appropriate techniques required to do well in the practical exams". This supports the findings of Maloney et al (2013c) who discussed the use of an online physiotherapy database which was accessed more during periods when exam preparation was foremost.…”
Section: Handling and Techniquesupporting
confidence: 84%
“…A second year student (15) explained in relation to question one that the LC "Offers guidance of the appropriate techniques required to do well in the practical exams". This supports the findings of Maloney et al (2013c) who discussed the use of an online physiotherapy database which was accessed more during periods when exam preparation was foremost.…”
Section: Handling and Techniquesupporting
confidence: 84%
“…This means nurses can now access information at point of care in real time, rather than needing to go to a library, a nurses' station, an office, or a university campus or to return home before being able to search for the information required. However, preparation and training within nursing courses, and easy access to and availability of the Internet in the workplace is required to enable convenient, timely access to information that can improve health outcomes of patients and augment nursing practice by promoting transfer of digital knowledge in the workplace [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Maloney et al showed that medical students appreciate the benefit of online repositories of learning resources [43]. They also showed that milestones of the curriculum (eg, examinations) often trigger access to the repositories.…”
Section: Discussionmentioning
confidence: 99%